2014
DOI: 10.1002/acr.22320
|View full text |Cite
|
Sign up to set email alerts
|

Finger Length Pattern as a Biomarker for Osteoarthritis and Chronic Joint Pain: A Population‐Based Study and Meta‐Analysis After Systematic Review

Abstract: Objective. Type 3 finger length pattern (longer fourth digit than second digit) is influenced by prenatal androgens and has been studied previously as a biomarker for sexually dimorphic traits. Because osteoarthritis (OA) and chronic pain are known to be sexually dimorphic traits, we evaluated the association between finger length pattern and OA and chronic joint pain. Methods. This study was part of the Rotterdam Study, a prospective population-based cohort study. We examined 4,784 participants. Associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
0
7
0
9
Order By: Relevance
“…Type 3 finger length pattern, an indicator of prenatal androgen exposure, was associated with symptomatic (but not radiographic) knee OA, chronic pain, and hand OA in the Rotterdam Study (21). Almost half of the association between elevated BMI and knee OA was explained by serum leptin level in the Maintenance of Balance, Independent Living, Intellect, and Zest in the Elderly Boston Study (22).…”
Section: Resultsmentioning
confidence: 99%
“…Type 3 finger length pattern, an indicator of prenatal androgen exposure, was associated with symptomatic (but not radiographic) knee OA, chronic pain, and hand OA in the Rotterdam Study (21). Almost half of the association between elevated BMI and knee OA was explained by serum leptin level in the Maintenance of Balance, Independent Living, Intellect, and Zest in the Elderly Boston Study (22).…”
Section: Resultsmentioning
confidence: 99%
“…We have identified several factors associated to pain, which were not related to structural damage of the joints [ 200 ]. We demonstrated that type 3 finger length pattern, an indicator of prenatal androgen exposure, was associated with having symptomatic knee OA, and chronic pain [ 201 ].…”
Section: Endocrine and Locomotor Diseasesmentioning
confidence: 99%
“…Another example is finger length pattern, which is thought to be an indicator of prenatal androgen exposure. Type 3 finger length pattern (longer fourth digit than second digit) has been associated with having symptomatic knee OA and chronic pain, which might be explained by an influence of embryogenic sex hormone exposure on brain development …”
Section: Epigenetic Programming During Developmentmentioning
confidence: 99%